A survival analysis on the drivers of the legalization of same-sex marriage - Diet, Kimberly Belle C. (School of Economics, University of the Philippines Diliman, 2019)
This paper aims to examine what factors _ political, economic, religious, and sociocultural _ drive countries to legalize same_sex marriage. The study employs a Cox Proportional_Hazards model to analyze how these different variables affect the probability to legalize same_sex marriage. From the 25 countries where same_sex marriage is officially legal as of 2018, the model showed that higher share of females in parliamentary seats favored legalization, while higher educational attainment for males was detrimental to legalization. These results suggest that countries with more female political representation have more inclusive policies, hence are more likely to pronounce same_sex marriage as lawful. On the contrary, a higher share of educated males is proven to reduce the risk of legalization, suggesting that secondary education does not markedly lessen negative public attitudes from men. This indicates a country_s overall socio_political condition and social equality have a strong influence on the legal acceptance of LGBTs.